IMMOBILIZATION OF SMALL PROTEINS IN CARBON NANOTUBES - HIGH-RESOLUTION TRANSMISSION ELECTRON-MICROSCOPY STUDY AND CATALYTIC ACTIVITY - Tsang, S; Davis, J; Green, M; Allen, H; Hill, O; Leung, Y; Sadler, P (1995)
The morphologies of the small proteins Zn2Cd5- metallothionein, cytochrome c3 and β-lactamase I immobilized inside carbon nanotubes have been studied by high-resolution transmission electron microscopy (HRTEM); single protein molecules and their associated forms were clearly observed inside the central cavity and a significant amount remained catalytically active indicating that no drastic conformational change had taken place.